Pseudomonas Exotoxin A: optimized by evolution for effective killing - Michalska, Marta; Wolf, Philipp (Frontiers in Microbiology, 2015)
Pseudomonas Exotoxin A (PE) is the most toxic virulence factor of the pathogenic bacterium Pseudomonas aeruginosa. This review describes current knowledge about the intoxication pathways of PE. Moreover, PE represents a remarkable example for pathoadaptive evolution, how bacterial molecules have been structurally and functionally optimized under evolutionary pressure to effectively impair and kill their host cells.